2020
DOI: 10.3390/jintelligence8020026
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Executive Functions in Predicting Mathematical Creativity in Typical Elementary School Classes: A Twofold Role for Updating

Abstract: The goal of the current study was to investigate the role of executive functions in mathematical creativity. The sample included 278 primary school children (ages 8–13). Two models were compared: the starting model tested whether executive functions (shifting, updating, and inhibition), domain-general creativity, and mathematical ability directly predicted mathematical creativity. The second model, which fitted the data best, included the additional assumption that updating influences mathematical creativity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 97 publications
(183 reference statements)
3
15
2
Order By: Relevance
“…General creativity is thought to help individuals to combine ideas and consider alternative approaches to a situation in original ways ( Pitta-Pantazi et al 2018 ). While recent studies in children suggested that general creativity and mathematical competence are almost equally important for mathematical creativity ( Schoevers et al 2018 ; Stolte et al 2020 ), our results revealed general creativity as the strongest predictor for mathematical creativity. However, the results are not completely consistent.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…General creativity is thought to help individuals to combine ideas and consider alternative approaches to a situation in original ways ( Pitta-Pantazi et al 2018 ). While recent studies in children suggested that general creativity and mathematical competence are almost equally important for mathematical creativity ( Schoevers et al 2018 ; Stolte et al 2020 ), our results revealed general creativity as the strongest predictor for mathematical creativity. However, the results are not completely consistent.…”
Section: Discussioncontrasting
confidence: 99%
“…However, the correlation we found was considerably smaller ( r = 0.24), also in comparison to a sample of college students ( r = 0.35, Chen et al 2006 ), and did not significantly predict mathematical creativity scores beyond the other measures. A similar finding was recently reported by Stolte et al ( 2020 ) with a small manifest correlation ( r = 0.20) between mathematical ability and mathematical creativity, which became statistically insignificant when taking into account other factors in an SEM. Our finding could be partly explained by the high correlation between the sub-facets of intelligence and mathematical competence.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations